2006
DOI: 10.1167/iovs.05-1235
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Lutein and Zeaxanthin and Other Carotenoids as Modifiable Risk Factors for Age-Related Maculopathy and Cataract: The POLA Study

Abstract: These results are strongly suggestive of a protective role of the xanthophylls, in particular zeaxanthin, for the protection against ARM and cataract.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
132
1
6

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(145 citation statements)
references
References 40 publications
6
132
1
6
Order By: Relevance
“…There is currently not Recommended Dietary Allowance RDA or Recommended Daily Intake RDI for lutein and zeaxanthin but some experts say you should ingest at least 4-6 milligrams mg of these carotenoids per day for beneficial effects 20,21 . Thus, in this study we managed to obtain 50.5 mg/kg in olive oil enriched from spinach 24 hour; 75:25 ratio in addition to the recommended daily amount of virgin olive oil of 23 grames 11 .…”
Section: Resultsmentioning
confidence: 99%
“…There is currently not Recommended Dietary Allowance RDA or Recommended Daily Intake RDI for lutein and zeaxanthin but some experts say you should ingest at least 4-6 milligrams mg of these carotenoids per day for beneficial effects 20,21 . Thus, in this study we managed to obtain 50.5 mg/kg in olive oil enriched from spinach 24 hour; 75:25 ratio in addition to the recommended daily amount of virgin olive oil of 23 grames 11 .…”
Section: Resultsmentioning
confidence: 99%
“…Xanthophylls act as antioxidants and shield ocular structures from blue light, which causes retinal injury leading to AMD ( 6 , 7 ). Previously, numerous studies showed that lutein has the potential to delay the development of AMD (8)(9)(10)(11)(12)(13). Lutein and zeaxanthin have been described as protecting photoreceptors from apoptosis induced by oxidative stress in vitro ( 8 ).…”
mentioning
confidence: 99%
“…Johnson et al demonstrated that consumption of spinach and corn, which contain lutein, in the daily diet for 15 wk raised the serum lutein concentration ( 12 ). In addition, Delcourt et al showed that high plasma lutein and zeaxanthin concentrations were associated with a reduced risk of AMD ( 13 ). Continuous ingestion of vegetables rich in lutein might contribute to an increased serum lutein concentration, thereby lowering the risk of AMD.…”
mentioning
confidence: 99%
“…There is a small study, which suggests Lutein supplements can improve vision in the short term, 34 adding to the concern surrounding b-carotene in the AREDS preparation, this has lead to significant confusion.…”
Section: Macular Pigmentsmentioning
confidence: 99%